Efisiensi Emiten Properti dan Real estate yang Terdaftar di Indeks Saham Syariah Indonesia Tahun 2016-2020 - Fresma Sari, Indah; Effendi, Jaenal (Shafin: Sharia Finance and Accounting Journal, 2021)
This study aims to analyze the efficiency of property and real estate issuers listed in the Indonesia Sharia Stock Index (ISSI) during 2016-2020 period and the factors that influence it. In the first stage, the researcher analyzes the efficiency value of property and real estate issuers using Data Envelopment Analysis (DEA) method. In the second stage, the researcher analyzes the factors that influence the efficiency value of property and real estate issuers by using tobit regression. There are 16 issuers used in this study. The results showed that none of the issuers consistently achieved the perfect technical efficiency score (the efficiency score is equal to 1) during the study period. The same thing happened to the pure technical efficiency analysis and the efficiency scale results. The results of the tobit model regression showed that the Return on Assets (ROA) has significant positive effect and the exchange rate (LNKURS) has significant negative effect on the efficiency value of property and real estate issuers. Meanwhile, the Debt to Asset Ratio (DAR), company size (LNSIZE), and interest rate (BIRATE) do not have significant effect on the efficiency of property and real estate issuers.